Uji Efikasi Jamur Entomopatogen Beauveria bassiana Terhadap Mortalitas Hama Ulat Tritip (Plutella xylostella L.) Pada Tanaman Sawi (Brassica Juncea L.) - Permana, Anselmus Pramudya Andhika; Rizali, Akhmad; Aziza, Noor Laili (Agroekotek View, 2023)
Mustard (Brassica juncea. L) is a horticultural commodity that has good commercial and prospects. However, in the cultivation process, this plant experiences many obstacles, one of which is the attack of the caterpillar (Plutella xylostella L.) which is detrimental to farmers, which can cause damage of 54-83%, so further handling is needed using the entomopathogenic fungus B. bassiana to control the damage caused by pest attacks. This study aims to determine the best concentration of B. bassiana in increasing mortality of tritip caterpillar (P. xylostella). This research was conducted at the Agroecotechnology Integrated Laboratory of the Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru, South Kalimantan from August - October 2020. This study used a completely randomized design (CRD) with a single factor treatment consisting of six treatments and four replications. So that the total number of 24 experimental units is obtained. The observation parameters in the study were the mortality percentage of the caterpillar pest (Plutella xylostella L.) and the mean time of death of the caterpillar pest (Plutella xylostella L.). The application of the entomopathogenic fungus B. bassiana had a significant effect on the mortality of the caterpillar pest. The best dose to increase the mortality of tritip caterpillar was found in treatment b5 B. bassiana with a dose of 2.5 g / 100 mL aquades with a mortality percentage of 97.5% and the fastest mean time of death was obtained in treatment b4 b. bassiana with a dose of 2 g / 100 mL of distilled water with an average time of death of 2.1 days or 50.4 hours.